2023
DOI: 10.1038/s41550-023-02125-3
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-periodic sub-pulse structure as a unifying feature for radio-emitting neutron stars

Michael Kramer,
Kuo Liu,
Gregory Desvignes
et al.

Abstract: Magnetars are highly magnetized rotating neutron stars that are predominantly observed as high-energy sources. Six of this class of neutron star are known to also emit radio emission, so magnetars are a favoured model for the origin of at least some of the fast radio bursts (FRBs). If magnetars, or neutron stars in general, are indeed responsible, sharp empirical constraints on the mechanism producing radio emission are required. Here we report on the detection of polarized quasi-periodic substructure in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…With periodicities between a dozen and more than 100 days found in repeating FRBs, there is now a consensus that the burst periodicity is associated with either the orbital periods of binary systems, with the companion being a degenerate star or massive star, or the precession of a magnetar (Levin et al 2020;Du et al 2021;Rajwade & van den Eijnden 2023). And the possible origin of an ultra-longperiod neutron star cannot be ruled out for FRBs with shorter periods (Beniamini et al 2020;Kramer et al 2023;Beniamini et al 2023).…”
Section: Possible Origin Of the Radio Emissionmentioning
confidence: 99%
“…With periodicities between a dozen and more than 100 days found in repeating FRBs, there is now a consensus that the burst periodicity is associated with either the orbital periods of binary systems, with the companion being a degenerate star or massive star, or the precession of a magnetar (Levin et al 2020;Du et al 2021;Rajwade & van den Eijnden 2023). And the possible origin of an ultra-longperiod neutron star cannot be ruled out for FRBs with shorter periods (Beniamini et al 2020;Kramer et al 2023;Beniamini et al 2023).…”
Section: Possible Origin Of the Radio Emissionmentioning
confidence: 99%
“…Some FRBs have been observed to exhibit quasi-periodicity, which does not appear to be related to a spin period (Chime/Frb Collaboration et al 2022;Pastor-Marazuela et al 2023). Observations of pulsars and magnetars have shown that quasi-periodic temporal structures can originate with frequencies orders of magnitude higher than the spin period (e.g., Kramer et al 2023), but such bursts present very differently in the polarization domain, showing flat PA curves in stark contrast to FRB 20210912A and FRB 20181112A. However, the existence of two remarkably similar FRBs suggests that at least a subclass of FRBs may originate in near-maximally rotating neutron stars, although identification of such events may not always be possible owing to various possible reasons discussed in Appendix F.…”
Section: A Possible Subclass Of Frbs?mentioning
confidence: 99%